F@ust vers. 3.0: A (Hi)story of Theatre and Media - Kati Röttger (Cultura, Lenguaje y Representación, 2009)
The article illuminates Goethe’s Faust (1 and 2) by tracing the theoretical conceptualization of an intermedial approach to theatre and performance, and argues for a historical dimension to the medial constitution of perception. While Goethe used the Faust-legend in his play to highlight two competitive orders of knowledge and media by presenting, on the one hand, the romantic, electric, and Mephistotelian ways of seeing and, on the other hand, the classic, literal and scientific order of knowledge; the Catalan theatre group Fura dels Baus transfer this conflict to the digital age in their remediation of the Faustlegend on the contemporary stage.